Evaluation of corneal dendritic cell density and subbasal nerve density in contact lens wearers using IVCM: A systematic review and meta-analysis - Guo, Rongjie; Jiang, Jiaxuan; Zhang, Yanan; Liang, Qi; Chen, Taige; Hu, Kai (Frontiers in Medicine, 2023)
Purpose To evaluate the subclinical changes in corneal dendritic cell density (CDCD) and corneal subbasal nerve density (CSND) in asymptomatic contact lens (CL) wearers. Methods Databases including PubMed, Scopus, Web of Science, and Cochrane Central Register of Controlled Trials were searched for trials and studies reporting the changes of corneal CDCD and CSND in contact lens wearers published until 25 June 2022. PRISMA guidelines as well as recommended meta-analysis practices were followed. Meta-analysis was conducted using RevMan V.5.3 software. Results After the screening, 10 studies with 587 eyes of 459 participants were included. Seven studies reported the data of CDCD. Compared with the control group, CDCD in the CL wearers was higher (18.19, 95% CI 18.8–27.57, p = 0.0001). Type of in vivo confocal microscopy (IVCM), wear duration, and frequency of lens change were sources of heterogeneity. The difference in CSND between CL wearers and the control group was insignificant, and subgroup analysis did not reveal a source of heterogeneity. Conclusion Overall, CDCD increased in CL wears, while CSND did not show significant differences. IVCM is a feasible tool to assess subclinical changes in CL wearers.